Normalisation d’un conte breton : à la recherche de l’impossible norme - Francis Favereau (La Bretagne Linguistique, 1996)
Which orthographic norm should be used to take into account the particularities of local Breton and to restore the nuances of orality? In the absence of a single standard Breton, the transition from orality to a norm is made difficult. Based on a tale heard in Poullaouen from the mouth of a retired farmer born in 1910, the aim of this paper is to identify the main difficulties involved in transcribing such a text, which is therefore neither an ethnotext strictly speaking, nor a text of oral literature, but a personal oral creation in the register of "Sunday Breton", or, if one prefers, in a slightly sustained language.